SELECTED MYTHS IN RELATION TO BILINGUALISM - Lucie Durdilová (Listy klinicke logopedie, 2017)
We meet with bilingual education increasingly to a greater extent. Under the influence of enlarging experience during the years, the approaches to bilingual child education are slowly changing. The speech therapist is the person who can help parents to find appropriate method to support in pozitive way both languagues development in their child. The text below is not a comprehensive analysis of the issue, it presents selected questions only, with the effort of current responses. This text is for everyone who participate to bilingual children education, last but not least is for teachers and parents of these children.